Combined PRP and microfat graft for facial disability in systemic sclerosis. Issue 3 (September 2017) - Philandrianos, Cécile; Magalon, Jéremy; Daumas, Aurélie; Veran, Julie; Sabatier, Florence; Magalon, Guy; Granel, Brigitte
Introduction: Systemic sclerosis (SSc) is a rare autoimmune disease characterized by fibrosis and microvascular damage. Facial signs are frequent and include perioral skin thickening, facial atrophy and microstomia. Facial handicap is overlooked by physicians but when patients are questioned, they frequently declare discomfort and distress due to their facial disability and appearance. As ideal autologous filler, fat graft has previously been considered in the treatment of facial handicap in SSc. To enhance fat graft survival, we combined fat graft and autologous platelet-rich plasma. Cases Description: Two patients suffering from SSc with facial disability, facial skin thickening and aesthetic discomfort were treated with combined subcutaneous microinjection of autologous fat and platelet-rich plasma. Conclusions: Regular follow-up until 12 months showed that facial disability decreased, skin texture appeared softer, and mouth opening increased. Patients declared to be very satisfied from a functional and aesthetic point of view until their last follow-up at 12 months. Fat grafting is beneficial in the improvement of facial symptoms of patients with SSc, and the addition of platelet-rich plasma is a feasible, simple and safe method. Further studies are required to better assess the advantage on fat graft retention, trophicity and the lasting effect offered by this combined therapy.